ENDOSCOPIC SPINE SURGERY: REVIEW ARTICLE - Mohamad Abdelraouf Metwally Farrag, Radwan Nouby Mahmoud, Ali Hamdan, Omar Yousef Hammad (Chelonian Research Foundation, 2025)
Background: Endoscopic spine surgery has emerged as an effective treatment option for cases of lumbar disc prolapse and lumbar canal stenosis, offering reduced postoperative pain and faster recovery. Objectives: Highlight the different endoscopic spine surgery approaches and their indications and advantages. Methods: We have searched literatures in PubMed, google scholar and science direct from 1994 to 2024. Conclusion: Endoscopic spine surgery is safe and effective for treating lumbosacral radiculopathy due to lumbar disc prolapse and lumbar canal stenosis, offering significant pain relief and functional recovery.